2020
DOI: 10.1038/s41598-020-76473-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and validity of TLICS system for thoracolumbar spine injury

Abstract: In order to enhance the reliability of the application to clinical practice of the TLICS classification, we retrospectively reviewed the patients with thoracolumbar spine injuries who underwent magnetic resonance imaging (MRI) and analyzed the validity of the TLICS classification and the necessity of MRI. We enrolled 328 patients with thoracolumbar spine injury who underwent MRI. All patients were classified into conservative and operative treatment groups. The TLICS score of each group was analyzed and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 18 publications
0
14
0
6
Order By: Relevance
“…6 For example, Park et al retrospectively reviewed 328 patients with thoracolumbar injuries and found that TLICS matched the decision for conservative treatment in 95% of cases and for operative treatment in 84% of cases. 4 Interestingly, while Dawkins et al found high interrater reliability using TLICS in a study of 81 pediatric patients, the reliability decreased when MRI was used by surgeons for injury assessment. 7 Our study demonstrates that a data-driven algorithm can reliably detect a suspected disruption of the PLC, in most cases, without the need for MRI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 For example, Park et al retrospectively reviewed 328 patients with thoracolumbar injuries and found that TLICS matched the decision for conservative treatment in 95% of cases and for operative treatment in 84% of cases. 4 Interestingly, while Dawkins et al found high interrater reliability using TLICS in a study of 81 pediatric patients, the reliability decreased when MRI was used by surgeons for injury assessment. 7 Our study demonstrates that a data-driven algorithm can reliably detect a suspected disruption of the PLC, in most cases, without the need for MRI.…”
Section: Discussionmentioning
confidence: 98%
“…3 There are several thoracolumbar injury classification methods used for clinical decision support, including the Magerl, Denis, and McAfee classification systems. 4 Nonetheless, the decision to operate can be controversial given difficulties in predicting the stability of spine injuries and a lack of clear treatment guidelines. The Thoracolumbar Injury Classification and Severity Score (TLICS) was proposed in 2005 to provide a classification system that accounted for neurological deficits and spinal stability and is intended to provide guidelines for operative and nonoperative decision-making.…”
mentioning
confidence: 99%
“…Our delayed surgical intervention rate of 1.4% is much lower than previously reported literature ranging from 4.7% to 25%. 10,11,14,15 Figure 1…”
Section: Discussionmentioning
confidence: 99%
“…The TLICS score comprises three major components: morphology of the fracture (compression [11], burst [12], translational/rotational [13], distraction [14]), amount of neurologic involvement (intact [10], nerve root/complete cord [12], incomplete cord/cauda equina [13]), and injury to the posterior ligamentous complex (indeterminate/suspected injury [12], injury [13]). A more severe injury is represented by a higher TLICS score.…”
mentioning
confidence: 99%
“…12 Two studies, representing the second and third largest series, focused on TLJ where 59 (11.15%) of 529 patients were To4; 37 (62.71%) of To4 in the TLJ were operative (Table 4). 9,15 .…”
Section: Study Type and Levels Of Evidencementioning
confidence: 99%